Health inequality in adolescence. Does stratification occur by familial social background, family affluence, or personal social position? - AH Rimpelä; LK Koivusilta; SM Kautiainen (BMC, 2006)
Abstract Background Two new sets of stratification indicators - family's material affluence and adolescent's personal social position- were compared with traditional indicators of familial social position based on parental occupation and education for their ability to detect health inequality among adolescents. Methods Survey data were collected in the Adolescent Health and Lifestyle Survey in 2003 from nationally representative samples of 12-, 14- and 16-year-old Finns (number of respondents 5394, response rate 71%). Indicators of the familial social position were father's socio-economic status, parents' education, parents' labour market position. Indicators of material affluence were number of cars, vacation travels, and computers in the family, own room and amount of weekly spending money. Adolescent's personal social position was measured as school performance. Measures of health were long-standing illness, overweight, use of mental health services, poor self-rated health and number of weekly health complaints. Ordinal logistic regression analysis was applied to study the associations between stratification indicators and health variables. Results All three groups of indicators of social stratification showed inequality in health, but the strongest associations were observed with the adolescent's personal social position. Health inequality was only partly identifiable by the traditional indicators of familial social position. The direction of the inequality was as expected when using the traditional indicators or personal social position: adolescents from higher social positions were healthier than those from lower positions. The indicators of family's material affluence showed mainly weak or no association with health and some of the indicators were inversely associated, although weakly. Conclusion In addition to traditional indicators describing the socio-structural influences on the distribution of health among adolescents, indicators of family's material affluence should be further developed. Adolescents' personal social position should be included in the studies of health inequalities.